Mean absorption coefficients of He/Ar/N2/(C1−x−y, Nix, Coy) thermal plasmas for CNT synthesis. (9th December 2016) - Salem, D; Hannachi, R; Cressault, Y; Teulet, Ph; Béji, L
Abstract: In this paper, we present the mean absorption coefficients (MACs) calculated for plasma mixtures of argon–helium–nitrogen–carbon–nickel–cobalt at 60 kPa and in a temperature range from 1 kK to 20 kK. These coefficients have been computed under the assumption of a local thermodynamic equilibrium (LTE), isothermal plasma, including atomic and molecular continuum, molecular bands and lines radiation splitted into nine spectral intervals. The results show that the continuum absorption coefficients strongly depend on photodissociation and photoionization processes of the molecular species N2, CN and C2, with a significant effect on photodetachment processes of C − in a frequency interval lower than 1 × 10 15 Hz and for low temperature (<6 kK). While at high temperature, the main contribution in continuum absorption coefficient comes from radiative recombination processes except in the infrared region (<0.5 × 10 15 Hz) where the inverse bremsstrahlung represents the most important component in continuum processes for all temperature values. On the other hand, the calculation of MAC shows that the role of molecular continuum, molecular bands and line absorption of the neutral catalysis species Ni/Co are only important in a small range of temperature and in a few spectral bands located in visible and infrared regions, while at high temperature and in UV and visible regions, the foremost contributions to MAC come from atomic continuum and line absorption.